The Essence of Management in Healthcare Organizations and the Main Stages of Staff Management (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In healthcare institutions, the management of the employees of this institution is considered one of the most important tasks, and its content is the process of influencing the employees of this institution to increase their work efficiency and achieve the general goals of the institution.All people who work in health care institutions and perform their work in accordance with their duties and are engaged in the performance of appropriate labor duties are considered employees. The extent to which employees perform their duties is an important indicator that determines the future of a medical institution. Therefore, managers focus on the effective performance of employees. This article describes in detail the essence of management and the main stages of personnel management in health care institutions.